Improving Students’ Grammar Skill Through Student Centered Learning at ITATS - Agustini, Siti; Wardhani, Norita Prasetya; Amalina, Evy Nur (Jurnal Bahasa Inggris, 2018)
English is an International language which is used by so many people to interact with people from other countries. Good English ability is needed by students to support learning process and working after the students graduate from university. Grammar is a point of language. By knowing and understanding correct grammar, so, their English is better. The aim of this research was to give proposal of English learning to improve students' grammar ability. The method used was students’ center learning using presentation in the class. The materials were simple present and perfect, future simple tense, modal, comparative, and passive voice. This research was conducted on 33 students in ITATS. The result of this research was 87% of students got to increase score for post-test and 30% of students passed the score. Thus, students’ center learning method was effective to increase students' grammar ability.